Quantitative spectroscopic comparison of the optical properties of mouse cochlea microstructures using optical coherence tomography at 1.06 µm and 1.3 µm wavelengths - Tsai, Ting-Yen (Biomed Opt Express, 2021)
Currently, the cochlear implantation procedure mainly relies on using a hand lens or surgical microscope, where the success rate and surgery time strongly depend on the surgeon’s experience. Therefore, a real-time image guidance tool may facilitate the implantation procedure. In this study, we performed a systematic and quantitative analysis on the optical characterization of ex vivo mouse cochlear samples using two swept-source optical coherence tomography (OCT) systems operating at the 1.06-µm and 1.3-µm wavelengths. The analysis results demonstrated that the 1.06-µm OCT imaging system performed better than the 1.3-µm OCT imaging system in terms of the image contrast between the cochlear conduits and the neighboring cochlear bony wall structure. However, the 1.3-µm OCT imaging system allowed for greater imaging depth of the cochlear samples because of decreased tissue scattering. In addition, we have investigated the feasibility of identifying the electrode of the cochlear implant within the ex vivo cochlear sample with the 1.06-µm OCT imaging. The study results demonstrated the potential of developing an image guidance tool for the cochlea implantation procedure as well as other otorhinolaryngology applications.